Text encryption for lower text size: Design and implementation. (2023) - Vishnoi, Ankit; Aggarwal, Alok; Prasad, Ajay; Prateek, Manish; Aggarwal, Shalini
Abstract: For enterprises of all sizes and types in the IT sector, data security is essential. Data security is the process of giving databases and websites secure data privacy protections and preventing unauthorized data access. By encrypting digital data, software/hardware, and hard drives, unauthorized individuals or hackers can only access unreadable material, which is why encryption is a crucial data protection strategy. Data is produced by computing operations, which are then used to encrypt and send the data into the network. For low bandwidth channels, an encryption strategy has been put out in this work. The proposed method uses the properties of homomorphic transform to make it more unique and suitable for text encryption. Conversion of plain text to cipher text is done by using simple union and symmetric difference operators. Which makes it more reliable in terms of execution time.